Flexible negative pole piece, preparation method thereof, sodium-ion battery and application of sodium-ion battery

By combining Ge, MoS2 and carbon nanofibers, a flexible negative electrode sheet with MoS2@Ge/CNFs structure was prepared, which solved the problem of insufficient flexibility and electrochemical performance of the negative electrode sheet of existing sodium ion battery, and achieved the improvement of high magnification and stable cycling performance.

CN119673958APending Publication Date: 2025-03-21GUANGDONG HAISIDA NAXING TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311208343.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The negative electrode sheets of existing sodium ion batteries cannot meet the flexibility requirements, and the rate and cycle performance of sodium ion batteries are poor.

Method used

A flexible negative electrode sheet combined with Ge, MoS2 and carbon nanofibers (CNFs) was prepared by spinneret and hydrothermal reaction steps to form a MoS2@Ge/CNFs structure to improve electrochemical performance.

Benefits of technology

The preparation of flexible negative electrode sheets is realized, which significantly improves the rate performance and circulation performance of sodium ion batteries, and has high capacity density and good sodium storage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004456565260000211
    Figure BDA0004456565260000211
Patent Text Reader

Abstract

The invention relates to the field of sodium-ion batteries, and discloses a flexible negative pole piece, a preparation method thereof, a sodium-ion battery and an application of the sodium-ion battery. The negative electrode plate comprises a negative electrode current collector and a negative electrode material covering at least one surface of the negative electrode current collector; the negative electrode material comprises a flexible carbon nanofiber layer and MoS2 loaded on the surface of the flexible carbon nanofiber layer, wherein the flexible carbon nanofiber layer comprises carbon nanofibers and Ge (germanium). The negative electrode plate shows a flexible characteristic, and the prepared sodium ion battery shows excellent rate capability and stable cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion batteries, and in particular to a flexible negative electrode sheet and a preparation method thereof, and a sodium ion battery and applications thereof. Background Art

[0002] Lithium-ion batteries (LIBs) are a promising high-energy electrochemical power source with high energy density, excellent rate performance, and stable cycle performance. However, the lack of raw materials and safety risks have limited the development of lithium batteries. Sodium-ion batteries (SIBs) are expected to become an alternative to lithium-ion batteries due to the similar chemical properties of sodium to lithium, high availability, high potential, and low cost. However, the radius of sodium ions is larger than that of lithium ions, the diffusion kinetics are slower, the volume expansion is larger, and the electrochemical performance is poorer.

[0003] In order to facilitate life and pursue fashion, flexible electronic products and wearable devices present a huge market prospect. Conventional electrodes prepared by coating slurry on current collectors cannot meet the flexibility requirements of batteries. Therefore, there is an urgent need for a negative electrode sheet that exhibits flexible characteristics, and the prepared sodium ion battery has excellent rate performance and stable cycle performance. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem that the negative electrode sheet in the prior art cannot meet the flexibility requirements and the obtained sodium ion battery has poor rate performance and cycle performance, and to provide a flexible negative electrode sheet and a preparation method thereof and a sodium ion battery and its application. The negative electrode sheet combines Ge, MoS2 and carbon nanofibers (CNFs), successfully making up for the shortcomings of the current negative electrode flexible materials, which is beneficial to the embedding and extraction of sodium ions on the negative electrode sheet, and accelerates the conduction of sodium ions and electrons. The negative electrode sheet is used in a sodium ion battery, showing excellent electrochemical properties.

[0005] In order to achieve the above-mentioned objectives, the first aspect of the present invention provides a flexible negative electrode plate, wherein the negative electrode plate comprises: a negative electrode collector and a negative electrode material covered on at least one surface of the negative electrode collector; wherein the negative electrode material comprises: a flexible carbon nanofiber layer and MoS2 loaded on the surface of the flexible carbon nanofiber layer; wherein the flexible carbon nanofiber layer comprises carbon nanofibers and Ge.

[0006] A second aspect of the present invention provides a method for preparing a flexible negative electrode sheet, wherein the preparation method comprises the following steps:

[0007] S1, mixing a polymer, Ge and a solvent, spraying the obtained solution on the surface of the negative electrode current collector, and obtaining an electrospinning membrane after drying;

[0008] S2. In the presence of an inert gas, heating the electrospun membrane sheet for the first time to obtain a flexible electrospun membrane sheet;

[0009] S3, immersing the flexible electrospinning membrane in a mixed aqueous solution containing sodium molybdate and L-cysteine, and then performing a second heating to obtain the negative electrode sheet.

[0010] The third aspect of the present invention provides a flexible negative electrode sheet prepared by the preparation method provided by the present invention.

[0011] A fourth aspect of the present invention provides a sodium ion battery, wherein the battery comprises the flexible negative electrode sheet provided by the present invention

[0012] A fifth aspect of the present invention provides an application of the sodium ion battery provided by the present invention in at least one of the fields of electronic equipment, power tools, household appliance energy storage and low-power electric vehicles.

[0013] Through the above technical solution, the beneficial effects of the present invention are:

[0014] In the flexible negative electrode sheet provided by the present invention, a flexible carbon nanofiber layer is covered on at least one surface of the negative electrode current collector, and MoS2 is loaded on the outer surface of the flexible carbon nanofiber layer. Ge is dispersed in the flexible carbon nanofiber layer, which improves electronic conductivity and prevents agglomeration. In addition, due to the excellent mechanical properties and flexibility of germanium / carbon nanofibers (Ge / CNFs), efficient ion and electron transfer is maintained throughout the electrode. MoS2 is attached to Ge / CNFs to prepare MoS2@Ge / CNFs. In this structure, Ge nanoparticles and MoS2 nanoparticles with higher theoretical capacity increase the reversible capacity, while flexible CNFs prevent the agglomeration of Ge and MoS2 and improve the conductivity. MoS2 nanoparticles provide a large number of active sites and improve the diffusion of ions and electrons.

[0015] The MoS2@Ge / CNFs flexible negative electrode sheet prepared by the present invention has good sodium storage performance. When used as a sodium ion negative electrode, it exhibits the advantages of high capacity density, good rate performance, stable cycle performance, etc. The MoS2@Ge / CNFs flexible negative electrode sheet itself is flexible, and the entire preparation process is simple, controllable, and easy to operate, which greatly simplifies the preparation process of the sodium ion negative electrode sheet and meets the conditions for achieving industrialization.

[0016] In a preferred embodiment of the present invention, when preparing the negative electrode sheet, by selecting a suitable weight ratio of polyacrylonitrile to Ge, spinning conditions, first heating conditions, weight ratio of sodium molybdate to L-cysteine, and hydrothermal reaction conditions, the electrochemical properties of the prepared sodium ion battery, such as specific energy, rate performance, and cycle performance, are further improved. -1The specific energy at a current density of 1000 mAh g -1 Above 2000mA·g -1 The specific energy at the current density is 250-500mAh·g -1 Above 100mA·g -1 The specific energy retention rate after 5000 cycles at a current density of is above 50%. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] A first aspect of the present invention provides a flexible negative electrode plate, wherein the negative electrode plate comprises: a negative electrode current collector and a negative electrode material covered on at least one surface of the negative electrode current collector; wherein the negative electrode material comprises: a flexible carbon nanofiber layer and MoS2 loaded on the surface of the flexible carbon nanofiber layer; wherein the flexible carbon nanofiber layer comprises carbon nanofibers and Ge.

[0019] A flexible carbon nanofiber layer is covered on at least one surface of the negative electrode current collector, and MoS2 is loaded on the outer surface of the flexible carbon nanofiber layer. Ge is dispersed in the flexible carbon nanofiber layer, which improves electronic conductivity and prevents agglomeration. In addition, due to the excellent mechanical properties and flexibility of Ge / carbon nanofibers (Ge / CNFs), efficient ion and electron transfer is maintained throughout the electrode. MoS2 is attached to Ge / CNFs to prepare MoS2@Ge / CNFs. In this structure, Ge nanoparticles and MoS2 nanoparticles with higher theoretical capacity increase the reversible capacity, while the flexible carbon nanofibers prevent the agglomeration of Ge and MoS2 and improve the conductivity. MoS2 nanoparticles provide a large number of active sites and improve the diffusion of ions and electrons.

[0020] According to the present invention, preferably, based on the total weight of the negative electrode material, the contents of the carbon nanofibers and Ge in the flexible carbon nanofiber layer are 5.3-25wt% and 73-94.5wt%, respectively. The contents of the carbon nanofibers and Ge satisfy this range, so that Ge can be mixed into the flexible carbon nanofiber layer to exert a high theoretical specific capacity, and sufficient Ge has high ion diffusion rate and rate capability.

[0021] According to the present invention, preferably, based on the total weight of the negative electrode material, the content of MoS2 is 0.2-2wt%. The content of MoS2 satisfies this range, which can aggravate the rapid diffusion of ions and electrons, not only making up for the lack of low capacity of graphite, but also effectively solving the problems of poor stability and conductivity.

[0022] According to the present invention, preferably, the thickness of the flexible carbon nanofiber layer is 32-52 μm. The thickness of the flexible carbon nanofiber layer meets this range, which can better realize the insertion and extraction of sodium ions during the cycle, otherwise it will lead to excess or lack of negative electrode.

[0023] The thickness of the flexible carbon nanofiber layer refers to the thickness of the flexible carbon nanofiber layer covered on one surface of the negative electrode current collector (single side of the current collector). In the present invention, MoS2 penetrates into the surface of the internal electrospinning (flexible carbon nanofiber layer), and the thickness is negligible. Therefore, the thickness of the negative electrode material covered on one surface of the negative electrode current collector is equivalent to the thickness of the flexible carbon nanofiber layer.

[0024] Preferably, the negative electrode material covers both surfaces of the negative electrode current collector. The thickness of the current collector is 12-20 μm.

[0025] Preferably, the negative electrode current collector is aluminum foil.

[0026] The negative electrode sheet of the present invention has no marks or light transmission when bent, which indicates that the negative electrode sheet of the present invention has good flexibility.

[0027] According to the present invention, preferably, the carbon nanofibers are obtained by carbonizing polyacrylonitrile (PAN). Polyacrylonitrile has a high carbonization degree and can effectively carbonize PAN into carbon nanofibers (carbonization conversion rate 50-55wt%). If other materials are used, the carbon nanofiber content will be reduced and more raw materials will be wasted.

[0028] According to the present invention, preferably, the diameter of the carbon nanofibers is 150-250 nm.

[0029] A second aspect of the present invention provides a method for preparing a flexible negative electrode sheet, wherein the preparation method comprises the following steps:

[0030] S1, mixing a polymer, Ge and a solvent, spraying the obtained solution on the surface of the negative electrode current collector, and obtaining an electrospinning membrane after drying;

[0031] S2. In the presence of an inert gas, the electrospun membrane is first heated to obtain a flexible electrospun membrane (Ge / CNFs membrane);

[0032] S3, immersing the flexible electrospinning membrane in a mixed aqueous solution containing sodium molybdate and L-cysteine, and then performing a second heating to obtain the negative electrode sheet.

[0033] In S2, the electrospun membrane is first heated, the polymer is carbonized into carbon nanofibers (CNFs), and a Ge / CNFs membrane is obtained, in which Ge is dispersed in CNFs. In S3, sodium molybdate and L-cysteine ​​are dissolved in water, and the Ge / CNFs membrane is immersed in the solution and then secondly heated. Sodium molybdate and L-cysteine ​​undergo a hydrothermal reaction, so that the generated MoS2 is attached to the flexible Ge / CNFs membrane obtained in S2.

[0034] According to the present invention, preferably, the polymer is polyacrylonitrile.

[0035] The weight average molecular weight of polyacrylonitrile is not particularly limited in the present invention, as long as carbon nanofibers can be formed after carbonization. Preferably, the weight average molecular weight of polyacrylonitrile is 100,000-200,000 g / mol.

[0036] According to the present invention, preferably, in S1, in the solution, based on 1 g of the solvent, the total amount of the polymer and Ge is 0.125-0.625 g.

[0037] According to the present invention, preferably, when the mixing is performed, the weight ratio of the polymer to Ge is 1:(1-9).

[0038] According to the present invention, preferably, the conditions for the spinning include: an applied voltage of 10-20 kV, a distance from the spinneret to the negative electrode current collector of 10-20 cm, a feed rate of 0.5-1.5 mL / h, and a spraying density of 0.1-1 mg / cm 2 When the spinning conditions meet this range, a nanofiber layer with a moderate thickness can be obtained, otherwise the carbon nanofiber layer will be too thin or too thick.

[0039] After spinning, drying is performed to remove the solvent, thereby obtaining an electrospinning membrane. According to the present invention, preferably, the drying conditions include: a temperature of 80-120° C. and a drying time of 12-24 hours.

[0040] According to the present invention, preferably, in S1, the polymer and the solvent are first mixed to obtain a mixed solution 1, and then Ge and the mixed solution 1 are mixed to obtain a mixed solution 2, and the mixed solution 2 is spun on the surface of the negative electrode current collector.

[0041] According to the present invention, preferably, the solvent is selected from at least one of N,N-dimethylformamide (DMF), 1-methyl-2-pyrrolidone (NMP) and N,N-dimethylacetamide (DMAc).

[0042] According to the present invention, preferably, in S2, the temperature of the first heating is 600-1000° C., and the time is 1-5 h.

[0043] According to the present invention, preferably, the first heating process comprises: heating to 600-1000°C at a rate of 1-5°C / min, and performing the first heating at a temperature of 600-1000°C for 1-5h. Performing the first heating according to this process can effectively carbonize polyacrylonitrile into CNFs (carbon nanofibers).

[0044] According to the present invention, preferably, in S2, the inert gas is argon.

[0045] According to the present invention, preferably, in S3, the second heating temperature is 150-250° C. and the time is 12-36 hours. Under such conditions, the hydrothermal reaction can effectively attach MoS2 to the carbon nanofiber layer.

[0046] In order to dissolve sodium molybdate and L-cysteine ​​more quickly and efficiently, preferably, in the mixed aqueous solution, the total amount of sodium molybdate and L-cysteine ​​is 2.33-5 g based on 100 mL of water.

[0047] According to the present invention, preferably, in the mixed aqueous solution, the weight ratio of sodium molybdate to L-cysteine ​​is 1:(1.33-4). The weight ratio of sodium molybdate to L-cysteine ​​satisfies this range, and MoS2 can be generated more efficiently through hydrothermal reaction.

[0048] According to a preferred embodiment of the present invention, the method for preparing a flexible negative electrode sheet comprises the following steps:

[0049] S1. Dissolve polyacrylonitrile (PAN) with a weight average molecular weight of 100,000-200,000 g / mol in a solvent to prepare a PAN solution (mixed solution 1) in advance, then mix the Ge powder and the PAN solution, stir at high speed to disperse the Ge powder in the PAN solution, inject the obtained mixed solution 2 into a syringe, and spin on the surface of the negative electrode current collector aluminum foil. The spinning conditions are: applied voltage of 10-20 kV, the distance from the spinneret to the aluminum foil of 10-20 cm, the feed rate of 0.5-1.5 mL / h, and the spraying density of 0.1-1 mg / cm 2 The spun aluminum foil is placed in an oven and maintained at a temperature of 80-120°C for 12-24 hours to obtain an electrospun membrane; wherein,

[0050] In the mixed solution 2, based on 1 g of the solvent, the total amount of polyacrylonitrile and Ge is 0.125-0.625 g; the weight ratio of polyacrylonitrile to Ge is 1:(1-9).

[0051] S2. Place the electrospun membrane obtained in S1 in a sealed tube, and under the protection of inert gas, heat it to 600-1000°C at a rate of 1-5°C / min, perform the first heating of the electrospun membrane at a temperature of 600-1000°C, maintain it for 1-5h, and then cool it naturally to obtain a Ge / CNFs flexible electrospun membrane.

[0052] S3, dissolving sodium molybdate and L-cysteine ​​in water, transferring the mixed aqueous solution to a hydrothermal reactor, immersing the flexible electrospinning membrane obtained in S2 in the mixed aqueous solution, setting the reactor temperature to 150-250°C, performing a second heating, and maintaining for 12-36 hours to obtain a MoS2@Ge / CNFs flexible negative electrode sheet; wherein,

[0053] In the mixed aqueous solution, based on 100 mL of water, the total amount of sodium molybdate and L-cysteine ​​is 2.33-5 g; the weight ratio of sodium molybdate to L-cysteine ​​is 1:(1.33-4).

[0054] The third aspect of the present invention provides a flexible negative electrode sheet prepared by the preparation method provided by the present invention.

[0055] A fourth aspect of the present invention provides a sodium ion battery, wherein the battery comprises the flexible negative electrode sheet provided by the present invention.

[0056] According to the present invention, preferably, the battery further comprises a positive electrode sheet, an electrolyte and a separator; wherein the positive electrode sheet is a sodium foil.

[0057] According to the present invention, preferably, the electrolyte comprises a conductive salt and a solvent.

[0058] The diaphragm can be a glass fiber membrane, a dry membrane, a wet membrane or a coated membrane, etc. According to the present invention, preferably, the diaphragm is selected from a glass fiber membrane, a coated ceramic diaphragm, a polypropylene / polyethylene / polypropylene (PP / PE / PP) composite porous diaphragm.

[0059] According to the present invention, preferably, the conductive salt is selected from at least one of NaPF6, NaClO3, NaTFSI and NaFSI.

[0060] According to the present invention, preferably, the solvent is selected from at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), polycarbonate (PC) and fluorinated ethylene carbonate (FEC).

[0061] According to the present invention, preferably, the content of the conductive salt in the electrolyte is 1.2-2 mol / L.

[0062] According to the present invention, preferably, the battery is -1 The specific energy at a current density of 1000 mAh g -1 Above 2000mA·g -1 The specific energy at the current density is 250-500mAh·g -1 Above 100mA·g -1 The specific energy retention rate after 5000 cycles at a current density of is above 50%.

[0063] According to a preferred embodiment of the present invention, the preparation method of the sodium ion battery comprises: in a glove box filled with inert gas, using metallic sodium foil as the positive electrode, a negative electrode sheet cut to a suitable size as the negative electrode, a glass fiber membrane as a separator, NaClO3 as an electrolyte conductive salt, and a solvent as a mixed solvent of EC and DMC to prepare a CR2032 model button battery.

[0064] The fifth aspect of the present invention provides an application of the sodium ion battery provided by the present invention in at least one of the fields of electronic equipment, power tools, household appliance energy storage and low-power electric vehicles; in particular, in flexible electronic products and wearing devices.

[0065] The present invention will be described in detail below through examples and comparative examples. In the following examples and comparative examples, unless otherwise specified, all methods are conventional methods; and the reagents and materials used, unless otherwise specified, can be obtained from commercial sources.

[0066] The battery discharge specific energy and cycle test were tested using a Xinwei tester. After 5000 cycles, the battery discharge specific energy after 5000 cycles was recorded.

[0067] The following examples are used to illustrate the preparation of sodium ion batteries.

[0068] Example 1

[0069] Preparation of flexible negative electrode sheet:

[0070] S1. Dissolve 0.5 g of polyacrylonitrile (PAN) with a weight average molecular weight of 100,000 g / mol in 8 g of DMF solvent to prepare a PAN solution (mixed solution 1) in advance, then mix 4.5 g of Ge powder and PAN solution, stir at high speed to disperse the Ge powder in the PAN solution, inject the obtained mixed solution 2 into a syringe, and spin on the surface of the negative electrode current collector aluminum foil. The spinning conditions are: applied voltage of 16 kV, the distance from the spinneret to the aluminum foil is 16 cm, the feed rate is 1.1 mL / h, and the spraying density is 0.1 mg / cm 2The spun aluminum foil was placed in an oven and maintained at 110°C for 20 hours to obtain an electrospinning membrane; wherein, in the mixed solution 2, the total amount of polyacrylonitrile and Ge was 0.625 g based on the amount of DMF solvent being 1 g; and the weight ratio of polyacrylonitrile to Ge was 1:9.

[0071] S2. Place the electrospun membrane obtained in S1 in a sealed tube, and under argon protection, heat it to 800°C at a rate of 5°C / min, perform the first heating at 800°C, maintain it for 3 hours, and then cool it naturally to obtain a Ge / CNFs flexible electrospun membrane.

[0072] S3. Dissolve 0.5g sodium molybdate and 1g L-cysteine ​​in 50mL distilled water, transfer the mixed aqueous solution to a hydrothermal reactor, immerse the flexible electrospinning membrane obtained in S2 in the mixed aqueous solution, set the temperature of the reactor to 210°C, perform the second heating, and maintain it for 24h to obtain a MoS2@Ge / CNFs flexible negative electrode sheet; wherein, in the mixed aqueous solution, based on 100mL of water, the total amount of sodium molybdate and L-cysteine ​​is 3g; the weight ratio of sodium molybdate to L-cysteine ​​is 1:2.

[0073] The obtained negative electrode sheet has no marks and no light transmission when bent, and has good flexibility. The diameter of the CNFs filaments measured by electron microscopy is 150nm.

[0074] In the obtained MoS2@Ge / CNFs flexible negative electrode sheet, based on the total weight of the negative electrode material, the contents of carbon nanofibers, Ge and MoS2 are 5.3wt%, 94.5wt% and 0.2wt% respectively; the thickness of the negative electrode sheet is 80μm (the thickness of the aluminum foil is 16μm, and the thickness of the single-sided flexible carbon nanofiber layer is 32μm).

[0075] Preparation of sodium ion batteries:

[0076] In a glove box filled with argon, a CR2032 button battery was prepared using metallic sodium foil as the positive electrode, a negative electrode sheet cut to a suitable size as the negative electrode, a glass fiber membrane as a separator, NaClO3 as the electrolyte conductive salt (the content of NaClO3 in the electrolyte was 1.5 mol / L), and a mixed solvent of EC and DMC in a weight ratio of 1:1.

[0077] Example 2

[0078] Preparation of flexible negative electrode sheet:

[0079] S1. Dissolve 0.5 g of polyacrylonitrile (PAN) with a weight average molecular weight of 150,000 g / mol in 8 g of DMF solvent to prepare a PAN solution (mixed solution 1) in advance, then mix 2 g of Ge powder and PAN solution, stir at high speed to disperse the Ge powder in the PAN solution, inject the obtained mixed solution 2 into a syringe, and spin on the surface of the negative electrode current collector aluminum foil. The spinning conditions are: the applied voltage is 14 kV, the distance from the spinneret to the aluminum foil is 14 cm, the feed rate is 0.9 mL / h, and the spraying density is 0.28 mg / cm 2 The spun aluminum foil was placed in an oven and kept at 100°C for 16 hours to obtain an electrospinning membrane; wherein, in the mixed solution 2, the total amount of polyacrylonitrile and Ge was 0.3125 g based on the amount of DMF solvent being 1 g; and the weight ratio of polyacrylonitrile to Ge was 1:4.

[0080] S2. Place the electrospun membrane obtained in S1 in a sealed tube, and under argon protection, heat it to 900°C at a rate of 4°C / min, perform the first heating at 900°C, maintain it for 4 hours, and then cool it naturally to obtain a Ge / CNFs flexible electrospun membrane.

[0081] S3. Dissolve 0.5g sodium molybdate and 0.8g L-cysteine ​​in 50mL distilled water, transfer the mixed aqueous solution to a hydrothermal reactor, immerse the flexible electrospinning membrane obtained in S2 in the mixed aqueous solution, set the temperature of the reactor to 190°C, perform the second heating, and maintain it for 30 hours to obtain a MoS2@Ge / CNFs flexible negative electrode sheet; wherein, in the mixed aqueous solution, based on 100mL of water, the total amount of sodium molybdate and L-cysteine ​​is 2.6g; the weight ratio of sodium molybdate to L-cysteine ​​is 1:1.6.

[0082] The obtained negative electrode sheet has no marks and no light transmission when bent, and has good flexibility. The diameter of the CNFs filaments measured by electron microscopy is 170nm.

[0083] In the obtained MoS2@Ge / CNFs flexible negative electrode sheet, based on the total weight of the negative electrode material, the contents of carbon nanofiber, Ge and MoS2 are 10.2wt%, 89.15wt% and 0.65wt% respectively; the thickness of the negative electrode sheet is 88μm (the thickness of the aluminum foil is 16μm, and the thickness of the single-sided flexible carbon nanofiber layer is 36μm).

[0084] Preparation of sodium ion batteries:

[0085] In a glove box filled with argon, a CR2032 button battery was prepared using metallic sodium foil as the positive electrode, a negative electrode sheet cut to a suitable size as the negative electrode, a coated ceramic diaphragm as the diaphragm, NaPF6 as the electrolyte conductive salt (the content of NaPF6 in the electrolyte was 1.5 mol / L), and a mixed solvent of PC and FEC in a weight ratio of 1:1.

[0086] Example 3

[0087] Preparation of flexible negative electrode sheet:

[0088] S1. Dissolve 0.5 g of polyacrylonitrile (PAN) with a weight average molecular weight of 200,000 g / mol in 8 g of NMP solvent to prepare a PAN solution (mixed solution 1) in advance, then mix 1.17 g of Ge powder and PAN solution, stir at high speed to disperse the Ge powder in the PAN solution, inject the obtained mixed solution 2 into a syringe, and spin on the surface of the negative electrode current collector aluminum foil. The spinning conditions are: the applied voltage is 18 kV, the distance from the spinneret to the aluminum foil is 18 cm, the feed rate is 1.3 mL / h, and the spraying density is 0.46 mg / cm 2 The spun aluminum foil was placed in an oven and kept at 90°C for 24 hours to obtain an electrospinning membrane; wherein, in the mixed solution 2, based on the amount of NMP solvent being 1g, the total amount of polyacrylonitrile and Ge was 0.209g; and the weight ratio of polyacrylonitrile to Ge was 1:2.34.

[0089] S2. Place the electrospun membrane obtained in S1 in a sealed tube, and under argon protection, heat it to 700°C at a rate of 3°C / min, heat the electrospun membrane at 700°C for the first time, keep it for 2 hours, and then cool it naturally to obtain a Ge / CNFs flexible electrospun membrane.

[0090] S3. Dissolve 0.5g sodium molybdate and 1.33g L-cysteine ​​in 50mL distilled water, transfer the mixed aqueous solution to a hydrothermal reactor, immerse the flexible electrospinning membrane obtained in S2 in the mixed aqueous solution, set the temperature of the reactor to 230°C, perform the second heating, and maintain it for 18h to obtain a MoS2@Ge / CNFs flexible negative electrode sheet; wherein, in the mixed aqueous solution, based on 100mL of water, the total amount of sodium molybdate and L-cysteine ​​is 3.7g; the weight ratio of sodium molybdate to L-cysteine ​​is 1:2.66.

[0091] The obtained negative electrode sheet has no marks and no light transmission when bent, and has good flexibility. The diameter of the CNFs filaments measured by electron microscopy is 190nm.

[0092] In the obtained MoS2@Ge / CNFs flexible negative electrode sheet, based on the total weight of the negative electrode material, the contents of carbon nanofibers, Ge and MoS2 are 15.1wt%, 83.8wt% and 1.1wt%, respectively; the thickness of the negative electrode sheet is 96μm (the thickness of the aluminum foil is 16μm, and the thickness of the single-sided flexible carbon nanofiber layer is 40μm).

[0093] Preparation of sodium ion batteries:

[0094] In a glove box filled with argon, a CR2032 button battery was prepared using metallic sodium foil as the positive electrode, a negative electrode sheet cut to a suitable size as the negative electrode, a PP / PE / PP composite separator as the separator, NaTFSI as the electrolyte conductive salt (the content of NaTFSI in the electrolyte was 1.5 mol / L), and EC as the solvent.

[0095] Example 4

[0096] Preparation of flexible negative electrode sheet:

[0097] S1. Dissolve 0.5 g of polyacrylonitrile (PAN) with a weight average molecular weight of 100,000 g / mol in 8 g of NMP solvent to prepare a PAN solution (mixed solution 1) in advance, then mix 0.75 g of Ge powder and PAN solution, stir at high speed to disperse the Ge powder in the PAN solution, inject the obtained mixed solution 2 into a syringe, and spin on the surface of the negative electrode current collector aluminum foil. The spinning conditions are: the applied voltage is 12 kV, the distance from the spinneret to the aluminum foil is 12 cm, the feed rate is 0.7 mL / h, and the spraying density is 0.64 mg / cm 2 The spun aluminum foil was placed in an oven and kept at 120°C for 12 hours to obtain an electrospinning membrane; wherein, in the mixed solution 2, based on the amount of NMP solvent being 1g, the total amount of polyacrylonitrile and Ge was 0.156g; and the weight ratio of polyacrylonitrile to Ge was 1:1.5.

[0098] S2. Place the electrospun membrane obtained in S1 in a sealed tube, and under argon protection, heat it to 1000°C at a rate of 2°C / min, perform the first heating at 1000°C, maintain it for 5 hours, and then cool it naturally to obtain a Ge / CNFs flexible electrospun membrane.

[0099] S3. Dissolve 0.5 g of sodium molybdate and 2 g of L-cysteine ​​in 50 mL of distilled water, transfer the mixed aqueous solution to a hydrothermal reactor, immerse the flexible electrospinning membrane obtained in S2 in the mixed aqueous solution, set the temperature of the reactor to 170°C, perform the second heating, and maintain it for 36 hours to obtain a MoS2@Ge / CNFs flexible negative electrode sheet; wherein, in the mixed aqueous solution, the total amount of sodium molybdate and L-cysteine ​​is 5 g based on 100 mL of water; the weight ratio of sodium molybdate to L-cysteine ​​is 1:4.

[0100] The obtained negative electrode sheet has no marks and no light transmission when bent, and has good flexibility. The diameter of the CNFs filaments measured by electron microscopy is 210nm.

[0101] In the obtained MoS2@Ge / CNFs flexible negative electrode sheet, based on the total weight of the negative electrode material, the contents of carbon nanofibers, Ge and MoS2 are 20.4wt%, 78.05wt% and 1.55wt%, respectively; the thickness of the negative electrode sheet is 104μm (the thickness of the aluminum foil is 16μm, and the thickness of the single-sided flexible carbon nanofiber layer is 44μm).

[0102] Preparation of sodium ion batteries:

[0103] In a glove box filled with argon, a CR2032 button battery was prepared using metallic sodium foil as the positive electrode, a negative electrode sheet cut to a suitable size as the negative electrode, a glass fiber membrane as a separator, NaFSI as the electrolyte conductive salt (the content of NaFSI in the electrolyte was 1.5 mol / L), and DMC as the solvent.

[0104] Example 5

[0105] Preparation of flexible negative electrode sheet:

[0106] S1. Dissolve 0.5 g of polyacrylonitrile (PAN) with a weight average molecular weight of 150,000 g / mol in 8 g of DMAc solvent to prepare a PAN solution (mixed solution 1) in advance, then mix 0.5 g of Ge powder and PAN solution, stir at high speed to disperse the Ge powder in the PAN solution, inject the obtained mixed solution 2 into a syringe, and spin on the surface of the negative electrode current collector aluminum foil. The spinning conditions are: applied voltage of 20 kV, the distance from the spinneret to the aluminum foil is 20 cm, the feed rate is 1.5 mL / h, and the spraying density is 0.82 mg / cm 2 The spun aluminum foil was placed in an oven and kept at 80°C for 16 hours to obtain an electrospinning membrane; wherein, in the mixed solution 2, the total amount of polyacrylonitrile and Ge was 0.125 g based on the amount of DMAc solvent being 1 g; and the weight ratio of polyacrylonitrile to Ge was 1:1.

[0107] S2. The electrospun membrane obtained in S1 is placed in a sealed tube, and under the protection of argon, the temperature is raised to 600°C at a rate of 1°C / min, and the electrospun membrane is first heated at 600°C, maintained for 5 hours, and then naturally cooled to obtain a Ge / CNFs flexible electrospun membrane.

[0108] S3. Dissolve 0.5g sodium molybdate and 0.67g L-cysteine ​​in 50mL distilled water, transfer the mixed aqueous solution to a hydrothermal reactor, immerse the flexible electrospinning membrane obtained in S2 in the mixed aqueous solution, set the temperature of the reactor to 250°C, perform the second heating, and maintain it for 12h to obtain a MoS2@Ge / CNFs flexible negative electrode sheet; wherein, in the mixed aqueous solution, based on 100mL of water, the total amount of sodium molybdate and L-cysteine ​​is 2.34g; the weight ratio of sodium molybdate to L-cysteine ​​is 1:1.34.

[0109] The obtained negative electrode sheet has no marks and no light transmission when bent, and has good flexibility. The diameter of the CNFs filaments measured by electron microscopy is 230nm.

[0110] In the obtained MoS2@Ge / CNFs flexible negative electrode sheet, based on the total weight of the negative electrode material, the contents of carbon nanofibers, Ge and MoS2 are 25wt%, 73wt% and 2wt% respectively; the thickness of the negative electrode sheet is 110μm (the thickness of the aluminum foil is 16μm, and the thickness of the single-sided flexible carbon nanofiber layer is 47μm).

[0111] Preparation of sodium ion batteries:

[0112] In a glove box filled with argon, a CR2032 button battery was prepared using metallic sodium foil as the positive electrode, a negative electrode sheet cut to a suitable size as the negative electrode, a glue-coated ceramic diaphragm as the diaphragm, NaPF6 as the electrolyte conductive salt (the content of NaPF6 in the electrolyte was 1.5 mol / L), and PC as the solvent.

[0113] Example 6

[0114] Preparation of flexible negative electrode sheet:

[0115] S1. Dissolve 0.5 g of polyacrylonitrile (PAN) with a weight average molecular weight of 200,000 g / mol in 8 g of DMAc solvent to prepare a PAN solution (mixed solution 1) in advance, then mix 0.5 g of Ge powder and PAN solution, stir at high speed to disperse the Ge powder in the PAN solution, inject the obtained mixed solution 2 into a syringe, and spin on the surface of the negative electrode current collector aluminum foil. The spinning conditions are: applied voltage of 10 kV, the distance from the spinneret to the aluminum foil is 10 cm, the feed rate is 0.5 mL / h, and the spraying density is 1 mg / cm 2The spun aluminum foil was placed in an oven and kept at 100°C for 16 hours to obtain an electrospinning membrane; wherein, in the mixed solution 2, the total amount of polyacrylonitrile and Ge was 0.125 g based on the amount of DMAc solvent being 1 g; and the weight ratio of polyacrylonitrile to Ge was 1:1.

[0116] S2. Place the electrospun membrane obtained in S1 in a sealed tube, and under argon protection, heat it to 600°C at a rate of 1°C / min, heat the electrospun membrane at 600°C for the first time, keep it for 1 hour, and then cool it naturally to obtain a Ge / CNFs flexible electrospun membrane.

[0117] S3. Dissolve 0.5g sodium molybdate and 0.67g L-cysteine ​​in 50mL distilled water, transfer the mixed aqueous solution to a hydrothermal reactor, immerse the flexible electrospinning membrane obtained in S2 in the mixed aqueous solution, set the temperature of the reactor to 150°C, perform the second heating, and maintain it for 24h to obtain a MoS2@Ge / CNFs flexible negative electrode sheet; wherein, in the mixed aqueous solution, based on 100mL of water, the total amount of sodium molybdate and L-cysteine ​​is 2.34g; the weight ratio of sodium molybdate to L-cysteine ​​is 1:1.34.

[0118] The obtained negative electrode sheet has no marks and no light transmission when bent, and has good flexibility. The diameter of the CNFs filaments measured by electron microscopy is 250nm.

[0119] In the obtained MoS2@Ge / CNFs flexible negative electrode sheet, based on the total weight of the negative electrode material, the contents of carbon nanofibers, Ge and MoS2 are 25wt%, 73wt% and 2wt% respectively; the thickness of the negative electrode sheet is 120μm (the thickness of the aluminum foil is 16μm, and the thickness of the single-sided flexible carbon nanofiber layer is 52μm).

[0120] Preparation of sodium ion batteries:

[0121] In a glove box filled with argon, a CR2032 button battery was prepared using metallic sodium foil as the positive electrode, a negative electrode sheet cut to a suitable size as the negative electrode, a PP / PE / PP composite diaphragm as the diaphragm, NaClO3 as the electrolyte conductive salt (the content of NaClO3 in the electrolyte was 1.5 mol / L), and FEC as the solvent.

[0122] Example 7

[0123] A sodium ion battery was prepared according to the method of Example 1, except that the weight ratio of polyacrylonitrile and Ge was different when preparing the negative electrode. Specifically, in S1, "mix 5g of Ge powder and PAN solution; in the mixed solution 2, based on the amount of DMF solvent used as 1g, the total amount of polyacrylonitrile and Ge was 0.688g; the weight ratio of polyacrylonitrile and Ge was 1:10" was used to replace "mix 4.5g of Ge powder and PAN solution; in the mixed solution 2, based on the amount of DMF solvent used as 1g, the total amount of polyacrylonitrile and Ge was 0.625g; the weight ratio of polyacrylonitrile and Ge was 1:9". A MoS2@Ge / CNFs flexible negative electrode was obtained, and then a CR2032 model button battery was obtained.

[0124] The obtained negative electrode sheet has no marks and no light transmission when bent, and has good flexibility. The diameter of the CNFs filaments measured by electron microscopy is 100nm.

[0125] In the obtained MoS2@Ge / CNFs flexible negative electrode sheet, based on the total weight of the negative electrode material, the contents of carbon nanofibers, Ge and MoS2 are 2.3wt%, 97.5wt% and 0.2wt% respectively; the thickness of the negative electrode sheet is 58μm (the thickness of the aluminum foil is 16μm, and the thickness of the single-sided flexible carbon nanofiber layer is 21μm).

[0126] Example 8

[0127] A sodium ion battery was prepared according to the method of Example 1, except that the spinning conditions were different. Specifically, in S1, "the applied voltage was 25 kV, the distance from the spinneret to the aluminum foil was 25 cm, and the feed rate was 1.8 mL / h" was used to replace "the applied voltage was 16 kV, the distance from the spinneret to the aluminum foil was 16 cm, and the feed rate was 1.1 mL / h". MoS2@Ge / CNFs flexible negative electrode sheet was obtained. Then a CR2032 model button battery was obtained.

[0128] The obtained negative electrode sheet has no marks and no light transmission when bent, and has good flexibility. The diameter of the CNFs filaments measured by electron microscopy is 120nm.

[0129] In the obtained MoS2@Ge / CNFs flexible negative electrode sheet, based on the total weight of the negative electrode material, the contents of carbon nanofibers, Ge and MoS2 are 5.3wt%, 94.5wt% and 0.2wt% respectively; the thickness of the negative electrode sheet is 64μm (the thickness of the aluminum foil is 16μm, and the thickness of the single-sided flexible carbon nanofiber layer is 24μm).

[0130] Example 9

[0131] A sodium ion battery was prepared according to the method of Example 1, except that in S2, "the electrospun membrane was first heated at a temperature of 1100°C, maintained for 2 hours, and then naturally cooled" was used to replace "the electrospun membrane was first heated at a temperature of 800°C, maintained for 3 hours, and then naturally cooled". A MoS2@Ge / CNFs flexible negative electrode was obtained. A CR2032 button battery was then obtained.

[0132] The obtained negative electrode sheet has no marks and no light transmission when bent, and has good flexibility. The diameter of the CNFs filaments measured by electron microscopy is 128nm.

[0133] In the obtained MoS2@Ge / CNFs flexible negative electrode sheet, based on the total weight of the negative electrode material, the contents of carbon nanofibers, Ge and MoS2 are 4.2wt%, 95.6wt% and 0.2wt% respectively; the thickness of the negative electrode sheet is 70μm (the thickness of the aluminum foil is 16μm, and the thickness of the single-sided flexible carbon nanofiber layer is 27μm).

[0134] Example 10

[0135] A sodium ion battery was prepared according to the method of Example 1, except that in S2, "heating to 800°C at a rate of 8°C / min" was used to replace "heating to 800°C at a rate of 5°C / min". A MoS2@Ge / CNFs flexible negative electrode sheet was obtained. A CR2032 model button battery was then obtained.

[0136] The obtained negative electrode sheet has no marks and no light transmission when bent, and has good flexibility. The diameter of the CNFs filaments measured by electron microscopy is 129nm.

[0137] In the obtained MoS2@Ge / CNFs flexible negative electrode sheet, based on the total weight of the negative electrode material, the contents of carbon nanofibers, Ge and MoS2 are 4.3wt%, 95.5wt% and 0.2wt% respectively; the thickness of the negative electrode sheet is 70μm (the thickness of the aluminum foil is 16μm, and the thickness of the single-sided flexible carbon nanofiber layer is 27μm).

[0138] Embodiment 11

[0139] A sodium ion battery was prepared according to the method of Example 1, except that the weight ratio of sodium molybdate and L-cysteine ​​was different. Specifically, in S3, "0.2g sodium molybdate and 1.3g L-cysteine ​​were dissolved in 50mL distilled water; the weight ratio of sodium molybdate and L-cysteine ​​was 1:6.5" was used to replace "0.5g sodium molybdate and 1g L-cysteine ​​were dissolved in 50mL distilled water; the weight ratio of sodium molybdate and L-cysteine ​​was 1:2". MoS2@Ge / CNFs flexible negative electrode was obtained. Then a CR2032 model button battery was obtained.

[0140] The obtained negative electrode sheet has no marks and no light transmission when bent, and has good flexibility. The diameter of the CNFs filaments measured by electron microscopy is 150nm.

[0141] In the obtained MoS2@Ge / CNFs flexible negative electrode sheet, based on the total weight of the negative electrode material, the contents of carbon nanofibers, Ge and MoS2 are 5.4wt%, 94.5wt% and 0.1wt% respectively; the thickness of the negative electrode sheet is 80μm (the thickness of the aluminum foil is 16μm, and the thickness of the single-sided flexible carbon nanofiber layer is 32μm).

[0142] Example 12

[0143] A sodium ion battery was prepared according to the method of Example 1, except that the total amount of sodium molybdate and L-cysteine ​​in the mixed aqueous solution was different. Specifically, in S3, "0.5g sodium molybdate and 1g L-cysteine ​​were dissolved in 50mL distilled water; in the mixed aqueous solution, based on 100mL of water, the total amount of sodium molybdate and L-cysteine ​​was 3g" was replaced by "1g sodium molybdate and 2g L-cysteine ​​were dissolved in 50mL of distilled water; in the mixed aqueous solution, based on 100mL of water, the total amount of sodium molybdate and L-cysteine ​​was 6g". A MoS2@Ge / CNFs flexible negative electrode was obtained. A CR2032 model button battery was then obtained.

[0144] The obtained negative electrode sheet has no marks and no light transmission when bent, and has good flexibility. The diameter of the CNFs filaments measured by electron microscopy is 150nm.

[0145] In the obtained MoS2@Ge / CNFs flexible negative electrode sheet, based on the total weight of the negative electrode material, the contents of carbon nanofibers, Ge and MoS2 are 5.3wt%, 94.42wt% and 0.18wt% respectively; the thickness of the negative electrode sheet is 80μm (the thickness of the aluminum foil is 16μm, and the thickness of the single-sided flexible carbon nanofiber layer is 32μm).

[0146] Embodiment 13

[0147] A sodium ion battery was prepared according to the method of Example 1, except that in S3, "the reactor temperature was set to 270°C" was used to replace "the reactor temperature was set to 210°C". A MoS2@Ge / CNFs flexible negative electrode sheet was obtained. A CR2032 model button battery was then obtained.

[0148] The obtained negative electrode sheet has no marks and no light transmission when bent, and has good flexibility. The diameter of the CNFs filaments measured by electron microscopy is 150nm.

[0149] In the obtained MoS2@Ge / CNFs flexible negative electrode sheet, based on the total weight of the negative electrode material, the contents of carbon nanofibers, Ge and MoS2 are 5.3wt%, 94.6wt% and 0.1wt% respectively; the thickness of the negative electrode sheet is 80μm (the thickness of the aluminum foil is 16μm, and the thickness of the single-sided flexible carbon nanofiber layer is 32μm).

[0150] Comparative Example 1

[0151] A sodium ion battery was prepared according to the method of Example 1, except that in S1, "4.5 g of Sn powder" was used to replace "4.5 g of Ge powder". A MoS2@Sn / CNFs flexible negative electrode sheet was prepared. A CR2032 model button battery was then prepared.

[0152] The obtained negative electrode sheet has no marks and no light transmission when bent, and has good flexibility. The diameter of the CNFs filaments measured by electron microscopy is 146nm.

[0153] In the obtained MoS2@Sn / CNFs flexible negative electrode sheet, based on the total weight of the negative electrode material, the contents of carbon nanofibers, Sn and MoS2 are 5.3wt%, 94.65wt% and 0.05wt% respectively; the thickness of the negative electrode sheet is 80μm (the thickness of the aluminum foil is 16μm, and the thickness of the single-sided flexible carbon nanofiber layer is 32μm).

[0154] Comparative Example 2

[0155] A sodium ion battery was prepared according to the method of Example 1, except that S3 was not performed, that is, the surface of the flexible carbon nanofiber layer was not loaded with MoS2, to obtain a Ge / CNFs flexible negative electrode sheet, and then a CR2032 model button battery was obtained.

[0156] The obtained negative electrode sheet has no marks and no light transmission when bent, and has good flexibility. The diameter of the CNFs filaments measured by electron microscopy is 150nm.

[0157] In the obtained Ge / CNFs flexible negative electrode sheet, based on the total weight of the negative electrode material, the contents of carbon nanofibers and Ge are 5.4wt% and 94.6wt% respectively; the thickness of the negative electrode sheet is 80μm (the thickness of the aluminum foil is 16μm, and the thickness of the single-sided flexible carbon nanofiber layer is 32μm).

[0158] Test Case

[0159] The CR2032 button batteries prepared in the examples and comparative examples were measured at 100 mA·g -1 The specific energy at a current density of 2000 mA g -1High rate specific energy at current density of 100 mA g -1 The specific energy retention rate after 5000 cycles at a current density of . The results are shown in Table 1.

[0160] Table 1

[0161]

[0162] The results in Table 1 show that the sodium ion batteries of Examples 1-13 have high specific energy, excellent rate performance and stable cycle performance. Comparative Example 1 replaces Ge with Sn, and the surface of the flexible carbon nanofiber layer of Comparative Example 2 does not load MoS2. Compared with Examples 1-13, the battery has a higher specific energy, excellent rate performance and stable cycle performance at 100 mA·g -1 and at 2000mA·g -1 The specific energy at a current density of 100 mA g -1 The specific energy retention rate decreased significantly after 5000 cycles at a current density of .

[0163] In addition, Example 7 changed the weight ratio of polyacrylonitrile and Ge, Example 8 changed the spinning conditions, Example 9 changed the carbonization temperature, Example 10 changed the heating rate, Example 11 changed the weight ratio of sodium molybdate and L-cysteine, Example 12 kept the ratio of sodium molybdate and L-cysteine ​​unchanged, but changed the concentration of sodium molybdate and L-cysteine, and Example 13 changed the hydrothermal reaction temperature. Compared with Example 1, the battery had a higher conductivity at 100 mA·g -1 and at 2000mA·g -1 The specific energy at a current density of 100 mA g -1 The specific energy retention rate decreased after 5000 cycles at a current density of . This indicates that the weight ratio of polyacrylonitrile and Ge, spinning conditions, carbonization conditions, weight ratio of sodium molybdate and L-cysteine, and hydrothermal reaction conditions jointly affect the electrochemical properties of the prepared sodium ion battery, such as specific energy and cycle performance.

[0164] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A flexible negative electrode sheet, characterized in that: The negative electrode plate includes: a negative electrode current collector and a negative electrode material covered on at least one surface of the negative electrode current collector; wherein the negative electrode material includes: a flexible carbon nanofiber layer and MoS2 loaded on the surface of the flexible carbon nanofiber layer; wherein the flexible carbon nanofiber layer includes carbon nanofibers and Ge.

2. The negative electrode sheet according to claim 1, characterized in that: Based on the total weight of the negative electrode material, in the flexible carbon nanofiber layer, the contents of the carbon nanofiber and Ge are 5.3-25wt% and 73-94.5wt% respectively; Preferably, based on the total weight of the negative electrode material, the content of MoS2 is 0.2-2wt%; Preferably, the thickness of the flexible carbon nanofiber layer is 32-52 μm.

3. The negative electrode sheet according to claim 1 or 2, characterized in that: The carbon nanofibers are obtained by carbonizing polyacrylonitrile; Preferably, the carbon nanofibers have a diameter of 150-250 nm.

4. A method for preparing a flexible negative electrode sheet, characterized in that: The preparation method comprises the following steps: S1, mixing a polymer, Ge and a solvent, spraying the obtained solution on the surface of the negative electrode current collector, and obtaining an electrospinning membrane after drying; S2. In the presence of an inert gas, heating the electrospun membrane sheet for the first time to obtain a flexible electrospun membrane sheet; S3, immersing the flexible electrospun membrane in a mixed aqueous solution containing sodium molybdate and L-cysteine, and then performing a second heating to obtain the negative electrode sheet; Preferably, the polymer is polyacrylonitrile.

5. The preparation method according to claim 4, characterized in that: In S1, in the solution, based on 1 g of the solvent, the total amount of the polymer and Ge is 0.125-0.625 g; Preferably, when the mixing is performed, the weight ratio of the polymer to Ge is 1:(1-9); Preferably, the conditions for the spinning include: an applied voltage of 10-20 kV, a distance from the spinneret to the negative electrode current collector of 10-20 cm, a feed rate of 0.5-1.5 mL / h, and a spraying density of 0.1-1 mg / cm 2 ; Preferably, the drying conditions include: temperature of 80-120° C. and time of 12-24 h.

6. The preparation method according to claim 4 or 5, characterized in that: In S1, the polymer and the solvent are first mixed to obtain a mixed solution 1, and then Ge and the mixed solution 1 are mixed to obtain a mixed solution 2, and the mixed solution 2 is spun on the surface of the negative electrode current collector; Preferably, the solvent is selected from at least one of N,N-dimethylformamide, 1-methyl-2-pyrrolidone and N,N-dimethylacetamide.

7. The preparation method according to any one of claims 4 to 6, characterized in that: In S2, the first heating temperature is 600-1000°C and the time is 1-5h; Preferably, in S3, the second heating temperature is 150-250° C. and the time is 12-36 hours; Preferably, in the mixed aqueous solution, the total amount of sodium molybdate and L-cysteine ​​is 2.33-5 g based on 100 mL of water; Preferably, in the mixed aqueous solution, the weight ratio of sodium molybdate to L-cysteine ​​is 1:(1.33-4).

8. A flexible negative electrode sheet obtained by the preparation method according to any one of claims 4 to 7.

9. A sodium ion battery, characterized in that: The battery comprises the flexible negative electrode sheet according to any one of claims 1 to 3 and 8; Preferably, the battery further comprises a positive electrode sheet, an electrolyte and a separator; wherein the positive electrode sheet is a sodium foil; Preferably, the electrolyte comprises a conductive salt and a solvent; Preferably, the diaphragm is selected from glass fiber membrane, rubber-coated ceramic diaphragm, polypropylene / polyethylene / polypropylene composite porous diaphragm; Preferably, the conductive salt is selected from at least one of NaPF6, NaClO3, NaTFSI and NaFSI; Preferably, the solvent is selected from at least one of ethylene carbonate, dimethyl carbonate, polycarbonate and fluorinated ethylene carbonate; Preferably, the content of the conductive salt in the electrolyte is 1.2-2 mol / L; Preferably, the battery is at 100 mA·g -1 The specific energy at a current density of 1000 mAh g -1 Above 2000mA·g -1 The specific energy at the current density is 250-500mAh·g -1 Above 100mA·g -1 The specific energy retention rate after 5000 cycles at a current density of is above 50%.

10. Use of the sodium ion battery according to claim 9 in at least one of electronic equipment, electric tools, household appliance energy storage and low-power electric vehicles.